Antimicrobial Resistance, Virulence Determinants, and Biofilm Formation of Enterococcus Species From Ready-to-Eat Seafood - Igbinosa, Etinosa O.; Beshiru, Abeni (Frontiers in Microbiology, 2019)
Enterococcus species form an important population of commensal bacteria and have been reported to possess numerous virulence factors considered significantly important in exacerbating diseases caused by them. The present study was designed to characterize antibiotic-resistant and virulent enterococci from ready-to-eat (RTE) seafood. A total of 720 RTE shrimp samples comprising sauced shrimp (n = 288), boiled shrimp (n = 216), and smoked shrimp (n = 216) obtained from open markets in Delta State, Nigeria, were assessed. Standard classical methods and polymerase chain reaction (PCR) were used in identifying the Enterococcus species. Potential virulence factors (β-hemolysis, gelatinase activity, S-layer, and biofilm formation) were assessed using standard procedures. The antibiotic susceptibility profile of the identified enterococci isolates was assayed using the Kirby–Bauer disc diffusion method. PCR was further used to screen selected antibiotic resistance and virulence genes. Prevalence of Enterococcus species from shrimp varieties is as follows: sauced, 26 (9.03%); boiled, 6 (2.78%); and smoked, 27 (12.50%), with an overall prevalence of 59 (8.19%) based on the occurrence of black hallow colonies after incubation. Enterococcus species detected include E. faecalis, 17 (28.8%); E. faecium, 29 (49.2%); E. gallinarum, 6 (10.2%); E. casseliflavus, 2 (3.4%); E. hirae, 3 (5.1%); and E. durans, 2 (3.4%). Biofilm occurrence among the shrimp varieties is as follows: 19/26 (73.1%) for sauced shrimps, 5/6 (83.3%) for boiled shrimps, and 16/27 (59.3%) for smoked shrimps. The phenotypic expression of the enterococci virulence revealed the following: S-layer, 59 (100%); gelatinase production, 19 (32.2%); and β-hemolysis, 21 (35.6%). An average of 3–11 virulence genes were detected in the Enterococcus species. The resistance profile of Enterococcus species is as follows: erythromycin, 29 (49.2%); vancomycin, 22 (37.3%); and tetracycline, 27 (45.8%). The frequency of occurrence of antibiotic resistance genes from the phenotypic resistant enterococci isolates to the macrolide, glycopeptide, and tetracycline antibiotics is as follows: ermA, 13/29 (44.8%); vanA, 14/22 (63.6%); tetA, 14/27 (51.9%); tetM, 15/27 (55.6%); ermB, 4/29 (13.8%); and vanB, 5/22 (22.7%). Findings from this study reveal the antibiotic resistance of enterococci strains of such species as E. durans, E. casseliflavus, E. gallinarum, and E. hirae. This study further revealed that RTE food products are reservoirs of potential virulent enterococci with antibiotic-resistant capabilities. This provides useful data for risk assessment and indicates that these foods may present a potential public health risk to consumers.